PaleoPhylo: free software to draw paleobiological phylogenies. Issue 3 (8th April 2009) - Ezard, Thomas H. G.; Purvis, Andy
Abstract : Paleobiological phylogenies often contain contrasting biological information to phylogenies based on extant species. Available software is primarily based on a present-day view of the world, however. Here, we present freeware to visualize phylogenies that is more suitable for the needs of paleobiologists, providing flexibility in how stratigraphic uncertainty, the geological timescale, and ancestor-descendant relationships are depicted.